Molecular Backgrounds of ERAP1 Downregulation in Cervical Carcinoma. (4th June 2015) - Mehta, Akash M.; Osse, Michelle; Kolkman-Uljee, Sandra; Fleuren, Gert Jan; Jordanova, Ekaterina S.
Abstract : The antigen processing machinery (APM) plays an important role in immune recognition of virally infected and transformed cells. Defective expression of the APM component ERAP1 is associated with progression and poor clinical outcome in cervical carcinoma. However, the underlying mechanisms of ERAP1 protein downregulation remain to be established. We investigated ERAP1 mRNA expression levels in 14 patients with established ERAP1 protein downregulation. To further examine the possible pretranscriptional mechanisms of ERAP1 downregulation, ERAP1 DNA mutation status was analyzed alongside existing data on various single nucleotide polymorphisms. Moreover, loss of heterozygosity at various loci in the ERAP1 gene was investigated. In cases with ERAP1 protein downregulation, ERAP1 mRNA quantities were found to be significantly lower than in a cohort with normal ERAP1 protein expression P = 0.001 . Loss of heterozygosity was demonstrated to occur in up to 50% of tumors with ERAP1 downregulation. Our data indicate that ERAP1 downregulation is associated with loss of heterozygosity. These data provide the first insight into in vivo mechanisms of ERAP1 downregulation in cervical carcinoma.